Motivation and Self-regulated Learning: A Case Study of a Pre-intermediate and an Upper-intermediate Adult Student - Mezei, Gabriella (Working Papers in Language Pedagogy, 2008)
The aim of this paper is to describe the self-regulation and motivational dispositions of two successful adult language learners at different proficiency levels in order to understand how motivational self-regulation and self-regulatory mechanisms in general shape their language learning behaviour. What motivated this research project was that self-regulation and motivation research lacks classroom-based descriptive studies; in addition, the Hungarian situation has hardly been studied yet. Devoting a case study to two successful language learners has allowed for a detailed description of their self-regulatory system with the tentative conclusions that self-regulatory capacity might be a function of proficiency and/or individual difference factors; furthermore the study has also provided evidence for self-regulation as a continuum.